2015
DOI: 10.5115/acb.2015.48.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma specific antigens, GD2 and CD90, are not involved in cancer stemness

Abstract: Glioblastoma multiforme (GBM) is the most malignant World Health Organization grade IV brain tumor. GBM patients have a poor prognosis because of its resistance to standard therapies, such as chemotherapy and radiation. Since stem-like cells have been associated with the treatment resistance of GBM, novel therapies targeting the cancer stem cell (CSC) population is critically required. However, GBM CSCs share molecular and functional characteristics with normal neural stem cells (NSCs). To elucidate differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…High CD90 expression was observed in high-grade gliomas [88][89][90][91]; however, conflicting results on the increased neurosphere-forming ability of CD90 + cells was reported by He et al [88] and Woo et al [91]. Nevertheless, both groups observed that CD90 + cells were distributed near the vasculature in the cancer tissue specimens which suggest their high metastatic ability and targeting CD90 might inhibit metastasis of glioma cells.…”
Section: Expression In Cancer-associated Stromal Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…High CD90 expression was observed in high-grade gliomas [88][89][90][91]; however, conflicting results on the increased neurosphere-forming ability of CD90 + cells was reported by He et al [88] and Woo et al [91]. Nevertheless, both groups observed that CD90 + cells were distributed near the vasculature in the cancer tissue specimens which suggest their high metastatic ability and targeting CD90 might inhibit metastasis of glioma cells.…”
Section: Expression In Cancer-associated Stromal Cellsmentioning
confidence: 90%
“…Woo et al in their recent study also found a significant overexpression of CD90 in 464T and 532T glioblastoma cells compared to the neural stem cells (cell lines 779, 682). However, they failed to find a significant difference in the in vitro tumor-forming ability between CD90 + and CD90 − populations separated from 464T glioblastoma cell line, contradicting the earlier findings and making room for further study in determining the role of CD90 in gliomas [91]. Nevertheless, Scognamiglio et al identified CD90 overexpression in atypical meningiomas (grade II) which are invasive tumors [92] and metastasize to lungs [93].…”
Section: Cd90 As Marker For Malignant Cancer Cellsmentioning
confidence: 93%
“…In a previous publication by Woo et al . [16], disialogangliosidase 2 (GD2) was identified as a GBM-specific antigen, in addition to a glycosphingolipid, CD90. As an initial screen, a variety of cell lines were assessed with respect to their relative expression of β4GANT 1 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…As an initial screen, a variety of cell lines were assessed with respect to their relative expression of β4GANT 1 mRNA. As a reference, we used cervical cancer HeLa cells, which have been shown to express β4GANT 1 [16]. Cell lines assessed included the colorectal HT29 and lung cancer A549 lines, expressing less or equivalent amounts of β4GANT 1 as the HeLa controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation